Comparison of the use of Tarompa E-Modules on Students' Environmental Care Characters - Syahrial; Asrial; Arsil; Yusra Dewi; Rahmi; Rahmat Perdana; Sabila Eka Septi; Fhadira Insani Putri (Universitas Pendidikan Ganesha, 2023)
Caring for the environment is a manifestation of human attitudes towards the environment in the form of everyday actions that attempt to prevent damage to the surrounding natural environment. This study aimed to analyze the use of the Tarompa e-module on the character of students who care about the environment and to find out whether the school has a significant difference from other schools. This type of quantitative research compares 4 schools with 17 students per class. The total number of students is 68 students. Data analysis techniques are descriptive statistical tests and inferential tests. The instrument in the study used a questionnaire. The results of this study show a significant difference in the use of the tarompa e-module on the character of caring for the environment. It can be concluded that the use of the pumped e-module is very beneficial for students because it can increase the students' environmental care character, and there is a significant comparison of the use of the tarompa e-module to the students' environmental care character in 4 elementary schools. This study implies that using the tarompa e-module can become a learning medium in schools, making it easier for teachers to choose good learning media.